RETRACTED: Neural Correlates of Handwriting Effects in L2 Learners - Li, Yifei; Guan, Connie Qun (Frontiers in Psychology, 2022)
Hand movement serves to link auditory and motor routines with visual word processing, which is a hallmark of successful reading. The current study aims to explore the effect of multisensory integration as a pathway to neural specialization for print among L2 Chinese and English readers. We identified L2 Chinese (n = 20) and L2 English (n = 20) adults on whom we conducted both behavioral and electroencephalogram (EEG) experiments. We designed six learning conditions: Hand Writing Chinese (HC), Viewing Chinese (VC), Drawing followed by Character Recognition in Chinese (DC), and Drawing followed by Word Recognition in English (DE). Both behavioral and EEG results showed that drawing facilitated visual word recognition in Chinese compared to viewing. The results of the study suggest benefits of hand movement on the neural processing and behavioral performance in response to Chinese character recognition for L2 Chinese leaners and English word recognition for L2 Chinese leaners. Furthermore, N170 amplitude at the drawing condition was positively correlated with N400 amplitude. Thus, the marker of early visual recognition (N170) was predictive of late semantic processing (N400).